Analysis of Rock Buttress in Landslide Remediation Method - Mohd Syukur Jamaludin (School of Environmental Engineering, University Malaysia Perlis, 2016)
To study the impact of difference surcharges on safety factor in rock buttress design using FEM. To study the effectiveness of rock buttress design in landslide remediation method with specific loading which is 15KN/m2.